Effects of illumination on capacitance characteristics of Au/3C-SiC/p-Si/Al diode - Kim, K. S.; Gupta, R. K.; Chung, G. S.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2011)
Au/3C-SiC/p-Si/Al Schottky barrier diode was prepared using atmospheric pressure chemical vapor deposition technique. The device parameters such as barrier height, ideality factor, and series resistance were calculated using current-voltage characteristics, and were found to be 0.44 eV, 1.55, and 1.02 x 10(4) ohm, respectively. The photocapacitive properties of the diode were studied under various illumination intensities. The transient photocapacitance measurements indicate that the capacitance of the Au/3C-SiC/p-Si/Al Schottky diode is very sensitive to illumination. The photocapacitance of the diode increases with increase in illumination intensity. The increase in photocapacitance with increase in illumination intensity suggests that these devices could be utilized as a photocapacitive sensor for optical sensors. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Poly 3C-SiC; Diode; Photocapacitance; Ideality factor; Barrier height